Evaluation of the Degradation Process of Diethyl (3H-1-Ethoxy-3-phenoxazinylidene) Ammonium Chloride in Water, after Exposure to Nonthermal Plasma at Atmospheric Pressure - Fidel Benjamín Alarcón Hernández; María del Carmen Fuentes Albarrán; José Luis Gadea Pacheco; Ángel Tlatelpa Becerro; Víctor Aristeo Cañete Cabrera (Journal of Chemistry)
The present study characterizes the degradation of diethyl dye (3H-1-ethoxy-3-phenoxazinylidene) ammonium chloride in water (concentration of 20.00 mg/L), after its exposure to nonthermal plasma of air at atmospheric pressure. The exposure time of the solution of interest to the plasma was 250 minutes per treatment. Four different nonthermal plasma generation conditions were considered (15, 20, 25, and 30 mA) at a voltage of 2000 V. The change in dilution was determined by UV/VIS spectrophotometry (absorbance and concentration), chemical oxygen demand (COD), pH, and bioassays with lettuce seeds (Lactuca sativa). Given the increase in temperature of the sample under study due to exposure to plasma, the change in each of the measured parameters was also explored as an exclusive function of the increase in temperature (27°C to 44°C). The measurements did not show the influence of temperature on the changes observed in the parameters of interest in this experiment. In general, the maximum degradation obtained from the samples analyzed at the end of the treatments corresponds to the 30 mA treatment. For this, reductions of 70.4% in absorbance, 71.5% of dye concentration, 81.6% of COD, and 51.85% of pH were achieved. The germination percentage of the lettuce seeds obtained was 74%. The degradation of the dye in the solution of interest depends on the plasma generating parameters high power and the high degradation rate.